Association of chronic heart failure with mortality in old intensive care patients suffering from Covid‐19. (10th March 2022) - Bruno, Raphael Romano; Wernly, Bernhard; Wolff, Georg; Fjølner, Jesper; Artigas, Antonio; Bollen Pinto, Bernardo; Schefold, Joerg C.; Kindgen‐Milles, Detlef; Baldia, Philipp Heinrich; Kelm, Malte; Beil, Michael; Sviri, Sigal; et al.
Abstract: Aims: Chronic heart failure (CHF) is a major risk factor for mortality in coronavirus disease 2019 (COVID‐19). This prospective international multicentre study investigates the role of pre‐existing CHF on clinical outcomes of critically ill old (≥70 years) intensive care patients with COVID‐19. Methods and results: Patients with pre‐existing CHF were subclassified as having ischaemic or non‐ischaemic cardiac disease; patients with a documented ejection fraction (EF) were subclassified according to heart failure EF: reduced (HFrEF, n  = 132), mild (HFmrEF, n  = 91), or preserved (HFpEF, n  = 103). Associations of heart failure characteristics with the 30 day mortality were analysed in univariate and multivariate logistic regression analyses. Pre‐existing CHF was reported in 566 of 3917 patients (14%). Patients with CHF were older, frailer, and had significantly higher SOFA scores on admission. CHF patients showed significantly higher crude 30 day mortality [60% vs. 48%, P  < 0.001; odds ratio 1.87, 95% confidence interval (CI) 1.5–2.3] and 3 month mortality (69% vs. 56%, P  < 0.001). After multivariate adjustment for confounders (SOFA, age, sex, and frailty), no independent association of CHF with mortality remained [adjusted odds ratio (aOR) 1.2, 95% CI 0.5–1.5; P  = 0.137]. More patients suffered from pre‐existing ischaemic than from non‐ischaemic disease [233 vs. 328 patients ( n  = 5 unknown aetiology)]. There were no differences in baseline characteristics between ischaemic and non‐ischaemic disease or between HFrEF, HFmrEF, and HFpEF. Crude 30 day mortality was significantly higher in HFrEF compared with HFpEF (64% vs. 48%, P  = 0.042). EF as a continuous variable was not independently associated with 30 day mortality (aOR 0.98, 95% CI 0.9–1.0; P  = 0.128). Conclusions: In critically ill older COVID‐19 patients, pre‐existing CHF was not independently associated with 30 day mortality. Trial registration number: NCT04321265.